Implicit cognitions on self-injurious and suicidal behavior in borderline personality disorder. (June 2023) - Scheunemann, Jakob; Kühn, Simone; Biedermann, Sarah V.; Lipp, Michael; Peth, Judith; Gallinat, Jürgen; Jelinek, Lena
Abstract: Background and objectives: Performance on implicit measures of suicidality has been associated with suicidal and nonsuicidal self-injury. Despite the high prevalence of self-harm in patients with borderline personality disorder (BPD), no previous study has assessed implicit measures in this patient group. Methods: Forty patients with BPD and 25 healthy controls completed three implicit association tests (IATs) (Death words – Me/Others words, Self-Harm pictures – Me/Others, and Self-Harm pictures – Good/Bad words) and a subliminal priming task (effect of the primes "dying"/"growing" on the categorization speed of positive/negative adjectives) as well as measures of psychopathology (suicidal ideation, previous nonsuicidal self-injury, borderline symptomatology, depression, and hopelessness). Results: Patients with BPD had higher scores on all three IATs than healthy controls. The subliminal priming procedure did not reveal group differences. Correlations between implicit measures and psychopathology among patients with BPD were mostly weak and nonsignificant with a few exceptions: Positive correlations were observed between IAT Self-Harm – Good/Bad and lifetime frequency of nonsuicidal self-injury, between IAT Self-Harm – Me/Others and depression, and between IAT Death – Me/Others and depression. Correlations between implicit measures were weak to moderate. Limitations: The study was cross-sectional only, and the study had reduced power as the sample size was limited. Conclusions: As expected, patients with BPD had higher scores than healthy controls on the IATs, which indicates higher implicit self-identification with self-harm and death as well as stronger implicit positive attitudes towards self-harm. The mostly weak correlations between implicit and explicit measures speak against the discriminative value of IATs in patients with BPD. Highlights: First investigation of patients with BPD using implicit measures of self-harm. Patients had higher implicit self-identification of self-harm/death than controls. Subliminal priming did not reveal group differences. Different implicit association tests correlated weakly/moderately with each other. Correlations between implicit cognitions and explicit measures were mixed.